Effect of Wind Tunnel Blockage on Aerodynamics of Circular Cylinders - Yousif, Saib Abdulla (Basrah Journal for Engineering Sciences, 2007)
Experimental investigation was conducted on low speed wind tunnel with (50 mm x100 mm) rectangular working section. Five smooth circular cylinders, as bluff bodies were applied. Cylinders diameters are 12.5, 15, 17, 35, and 37 mm which experience blockage ratio of 12.5%, 15%, 17%, 35%, and 37%, respectively. The range of Reynolds No. and air velocity for present study is 0.7x10^4-5x10^4 and 10-20 m/s respectively which are more applicable in engineering field. The experiments were carried out in fluid mechanics laboratory, Faculty of engineering and technology, Sebha University, Libya. Results indicate that cylinders of blockage ratio of 35% and 37% experience lower pressure coefficients around bodies, lower velocity distribution in the wake, and higher drag coefficients. Drag coefficient correction is agreed with unconfined flow for blockage ratio less than 17%. Wake and buoyancy blockages may have effect on models of higher blockage ratios.